Age-Related Alterations in Macrophage Distribution and Function Are Associated With Delayed Cutaneous Wound Healing - Dube, Christabel Thembela; Ong, Yasmin Hui Binn; Wemyss, Kelly; Krishnan, Siddharth; Tan, Tiak Ju; Janela, Baptiste; Grainger, John R.; Ronshaugen, Matthew; Mace, Kimberly A.; Lim, Chin Yan (Frontiers in Immunology, 2022)
Ageing-related delays and dysregulated inflammation in wound healing are well-documented in both human and animal models. However, cellular and molecular changes underlying this impairment in healing progression are not fully understood. In this study, we characterised ageing-associated changes to macrophages in wounds of young and aged mice and investigated transcriptomic differences that may impact the progression of wound healing. Full-thickness wounds created on the dorsum of C57BL/6J young and aged mice were excised on Days 3 and 7 post-wounding for analysis by immunohistochemistry, flow cytometry, and RNA sequencing. Our data revealed that macrophages were significantly reduced in aged wounds in comparison to young. Functional transcriptomic analyses showed that macrophages from aged wounds exhibited significantly reduced expression of cell cycle, DNA replication, and repair pathway genes. Furthermore, we uncovered an elevated pro-inflammatory gene expression program in the aged macrophages correlated with poor inflammation resolution and excessive tissue damage observed in aged wounds. Altogether, our work provides insights into how poorly healing aged wounds are phenotypically defined by the presence of macrophages with reduced proliferative capacity and an exacerbated inflammatory response, both of which are pathways that can be targeted to improve healing in the elderly.